2002
DOI: 10.1038/sj....bjc.6600209...
|View full text |Cite
|
Sign up to set email alerts
|

Patient delay and stage of diagnosis among breast cancer patients in Germany – a population based study

Abstract: Early diagnosis is a tenet in oncology and should enable early treatment with the expectation of improved outcome. Extent and determinants of patient delay of diagnosis in breast cancer patients and its impact on stage of disease were examined in a population based study among female breast cancer patients in Germany. Two hundred and eighty-seven women, aged 18 to 80 years with newly diagnosed invasive symptomatic breast cancer, were interviewed with respect to the diagnostic process. Patient delay was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
113
2
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(134 citation statements)
references
References 28 publications
14
113
2
5
Order By: Relevance
“…The patient's delay was longer in this and in the study of Kjellgren and Solheim [9] compared to the findings of Flam et al [10]. In several studies on breast cancer, long patient's delay was related to shorter survival; however, Thulesius and others [16][17][18] found no effect of patient's or doctor's delay on long-term survival of ovarian cancer patients. Some authors have claimed that women living in urban areas see their physicians earlier than women living in rural areas, probably because the former have easier access to health services but they may also be more concerned about their symptoms [10].…”
Section: Discussionmentioning
confidence: 61%
“…The patient's delay was longer in this and in the study of Kjellgren and Solheim [9] compared to the findings of Flam et al [10]. In several studies on breast cancer, long patient's delay was related to shorter survival; however, Thulesius and others [16][17][18] found no effect of patient's or doctor's delay on long-term survival of ovarian cancer patients. Some authors have claimed that women living in urban areas see their physicians earlier than women living in rural areas, probably because the former have easier access to health services but they may also be more concerned about their symptoms [10].…”
Section: Discussionmentioning
confidence: 61%
“…Obese women have been shown to be twice as likely to postpone doctor's visit for more than 3 months after occurrence of first symptoms, resulting in advanced stage of disease at presentation [42].…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic literature review published in 1999 and subsequent research, there is strong evidence of an association between older age and patient delay [5,6]. The systematic review found less strength of evidence for socioeconomic status and ethnicity and strong evidence that marital status was unrelated to patient delay.…”
Section: What Factors Contribute To Delay?mentioning
confidence: 95%